2019
DOI: 10.1167/tvst.8.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Malignancy in Ocular Surface Lesions by Inverse Spectroscopic Optical Coherence Tomography and Two-Photon Autofluorescence

Abstract: Purpose Advanced imaging is increasingly important in the diagnosis of ocular surface malignancy. Inverse spectroscopic optical coherence tomography (ISOCT) and two-photon autofluorescence microscopy (2P-AF) are emerging techniques capable of quantifying ultrastructural and metabolic changes, respectively. We aimed to detect malignancy in ocular surface lesions using ISOCT and 2P-AF. Methods Portions of excised specimens from patients undergoing conjunctival biopsy at B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The ability to detect and capture early metastases in these systems via ISOCT shows great potential for improving cancer therapeutics and interventions. Lee et al expanded upon these ideas by utilizing ISOCT and two-photon autofluorescence to quantify nanoscale ultrastructural and metabolic changes, respectively, in ocular surface lesions leading to ocular surface squamous neoplasia (OSSN) [46]. Their results suggested that lesions with increased malignant potential had a higher D (mass density measurement) and a decrease in the optical redox ratio (cancer association via increased cellular proliferation or differentiation), which collectively supported ultrastructural compaction and modifications.…”
Section: Optical Scattering and Inverse Spectroscopic Optical Coheren...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to detect and capture early metastases in these systems via ISOCT shows great potential for improving cancer therapeutics and interventions. Lee et al expanded upon these ideas by utilizing ISOCT and two-photon autofluorescence to quantify nanoscale ultrastructural and metabolic changes, respectively, in ocular surface lesions leading to ocular surface squamous neoplasia (OSSN) [46]. Their results suggested that lesions with increased malignant potential had a higher D (mass density measurement) and a decrease in the optical redox ratio (cancer association via increased cellular proliferation or differentiation), which collectively supported ultrastructural compaction and modifications.…”
Section: Optical Scattering and Inverse Spectroscopic Optical Coheren...mentioning
confidence: 99%
“…Their results suggested that lesions with increased malignant potential had a higher D (mass density measurement) and a decrease in the optical redox ratio (cancer association via increased cellular proliferation or differentiation), which collectively supported ultrastructural compaction and modifications. Consequently, they were able to differentiate between normal, premalignant and malignant tissue samples more readily [46].…”
Section: Optical Scattering and Inverse Spectroscopic Optical Coheren...mentioning
confidence: 99%
“…Optical coherence tomography (OCT) has been used for numerous indications in the diagnosis and management of ophthalmic disorders. [10][11][12][13] The advantage of OCT is the non-invasive and user friendly method. However, there are limited studies on their use in OSSN excision.…”
Section: Introductionmentioning
confidence: 99%